Replacement of chromosome 3D with Thinopyrum chromosome 3St led to increased drought tolerance during the flowering stage in wheat - Türkösi, Edina; Kruppa, Klaudia; Darkó, Éva; Varga, Balázs; György, Márton; Gulyás, Zsolt; Jobbágy, Kristóf; Holušová, Kateřina; Gaál, Eszter; Kalapos, Balázs; Cséplő, Mónika; Farkas, András; et al. (Plant cell reports, 2025)
The stable 3St(3D) substitution line offers promising genetic potential for improving drought tolerance in wheat during critical reproductive stages. The flowering stage is highly susceptible to drought, which significantly reduces wheat grain yield globally. Low genetic diversity in wheat further limits the discovery of optimal gene variants for breeding climate-resilient varieties. The substitution of chromosome 3D by a group 3 chromosome pair from Thinopyrum intermedium × Th. ponticum artificial hybrid was identified using in situ hybridization and genotyping-by-sequencing. This homoeologous substitution showed good functional compensation for grain yield and fertility, similar to the wheat parents ('Mv9kr1' and 'Mv Karizma') in field and greenhouse trials. The substitution line exhibits a semidwarf phenotype due to the Rht8 and Rht2 dwarfing alleles. Automated shoot phenotyping after a 10-day water withdrawal at flowering revealed efficient water preservation allowing to maintain photosynthetic functions, sustained photosynthetic activity, and less chlorophyll degradation, indicated by Normalized Difference Vegetation Index (NDVI) and modified Normalized Difference Index (mND705) values and moderate level of protective functions shown by the expression of stress-related genes. Compared to the wheat parents, the substitution line developed thicker roots with increased volume under drought, resulting in a lower surface-to-volume ratio. This may enhance water storage efficiency and help reduce yield loss under drought conditions.
Keywords: Flowers; květy; Plant Breeding; Phenotype; Triticum; odolnost proti suchu; Genotyping-by-sequencing coverage analysis; In situ hybridization; pšenice; fenotyp; Poaceae; šlechtění rostlin; Drought tolerance; Chromosomes, Plant; Agropyron glael; lipnicovité; Droughts; chromozomy rostlin; Drought Resistance; období sucha